The discourse of the epistemic community of artistic gymnastics: the analysis of articles titles - Omrcen, D.; Markovic, K. Z. (Science of Gymnastics Journal, 2009)
The goal of this study was to analyse 105 titles of articles published in 43 journals that are indexed in at least one of the three databases - ScienceDirect, MEDLINE and Scopus - in order to describe the epistemic community that deals with gymnastics-related topics. To analyse the collected data frequencies, Pearson Chi-square test and the hierarchical cluster analysis were used. The results showed that most articles were written by two or three authors, and that the titles written by two, three and four authors contained the largest number of words of Latin etymology. Words of Latin origin were used significantly more frequently than those of the English origin, whereas a word of Greek origin was used almost as frequently as a word of English origin. The word class most frequently used in the titles was the nouns. Neither the number of words of Latin origin per title nor the number of words of Greek origin differed significantly by the publication year. The cluster analysis showed that the principal cluster was formed of lexical words which were nouns predominantly of Latin origin. The results of this research showed that the scientific discourse of the analysed titles concurs with the basic principles of academic writing and that the epistemic community of artistic gymnastics can be identified by its specific vocabulary.